Modern architecture and Protestant religious expression: A theological proposal of Paul Tillich and the architectural expression of Fábio Penteado - Lima Jr., Marcio Antonio de (Actas de Arquitectura Religiosa Contemporánea, 2017)
In this communication we propose to explore the thought of the theologian Paul Tillich (1886-1965), who understands that arts in general and architecture in particular can stimulate the human spirit to see new angles of reality and existence. Modern architecture, in his opinion, could represent the Protestant religious character and constitute a real possibility of Protestant architectural creation, characterized by the community that meets to hear, thus achieving an honest expression of their faith. In dialogue with the thought of Paul Tillich, our proposal is to analyze how some of these points are reflected in the project for the Presbyterian National Church, Brasilia, in 1965, developed by the architect Fabio Penteado. This is characterized by the predominance of the wide cover built in exposed concrete and a spatial organization that provides the experience of the encounter of the human being and the transcendent